Adsorption of Methylene Blue Using Tea Waste Treated with Alkaline-Potassium Hydroxide - Shariena, Shamsul Bahari; Fify Nursuhanti, Jahid; Yuen, Mei Lian; Ros Azlinawati, Ramli; Ling, Lee Siew (Trans Tech Publications Ltd, 2022)
Textile dyes which are known to be poisonous, mutagenic, and carcinogenic to human health and the environment are found in water bodies, posing a severe environmental threat. The well-known adsorption approach, which uses low-cost agricultural waste as an adsorbent, has recently been extensively explored for water remediation. The ability of tea waste (Camellia Sinensis) species treated with alkaline-potassium hydroxide (KOH) to adsorb methylene blue (MB) dye from dye-contaminated wastewater was investigated. The influence of experimental parameters including pH, initial dye concentration and contact time, temperature and adsorbent dosages on the alkaline-KOH treated tea waste adsorption process were studied. SEM and FTIR were used to characterize the KOH treated tea waste adsorbent. The pH 10 condition was shown to be the best for attaining the highest percent of methylene blue removal. The optimal adsorption for methylene blue was greatly detected at 120 minutes of 100 mg/L. The removal of methylene blue was excellent at a temperature of 60o C and 0.1 g of KOH treated tea waste dose was chosen as the most favourable for the adsorption of methylene blue. Finally, the synthetic wastewater was examined under optimal conditions and recorded 97 % methylene blue removed.